2012
DOI: 10.1093/cercor/bhs224
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Visual Object and Word Recognition Relies on High Spatial Frequency Coding in the Left Posterior Fusiform Gyrus: Evidence from a Case-Series of Patients with Ventral Occipito-Temporal Cortex Damage

Abstract: Recent visual neuroscience investigations suggest that ventral occipito-temporal cortex is retinotopically organized, with high acuity foveal input projecting primarily to the posterior fusiform gyrus (pFG), making this region crucial for coding high spatial frequency information. Because high spatial frequencies are critical for fine-grained visual discrimination, we hypothesized that damage to the left pFG should have an adverse effect not only on efficient reading, as observed in pure alexia, but also on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 62 publications
9
107
0
Order By: Relevance
“…While a number of models can account for basic facts about acquired dyslexia, recent case-series data have indicated that these disorders are in fact more multi-faceted, dynamic and variable than previously thought [11][12][13]. This paper aims to demonstrate that these case-series data on acquired dyslexia can be best accommodated within connectionist models.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…While a number of models can account for basic facts about acquired dyslexia, recent case-series data have indicated that these disorders are in fact more multi-faceted, dynamic and variable than previously thought [11][12][13]. This paper aims to demonstrate that these case-series data on acquired dyslexia can be best accommodated within connectionist models.…”
Section: Introductionmentioning
confidence: 91%
“…As can be seen in figure 1b(i), patients with a severe reading disorder as a result of pFG lesions show very slow reading speeds that are unduly affected by letter length, in contrast to the rapid reading and negligible length effects shown by normal participants [31]. Although stroke lesions are variable and often extend beyond the pFG, voxel-based lesion symptom mapping has revealed that the length effect in reading is indeed associated with damage specifically to the pFG [11]. In terms of theoretical accounts of this disorder, debates have centred around the domain specificity of the functional cause, with some accounts proposing damage to readingspecific cognitive components housed in pFG, whereas the [11], with the scale representing the number of participants out of the total in that group with lesions in a given area.…”
Section: Pure Alexiamentioning
confidence: 97%
See 1 more Smart Citation
“…This position is supported by neuropsychological investigations of patients with acquired dyslexias, in which damage to visual, phonological, and semantic systems are associated with distinct patterns of reading deficit. The visually based reading deficit sometimes termed "pure alexia" is associated with damage to the left ventral occipitotemporal cortex (14,15), an area that is ubiquitously activated for tasks involving orthographic processing (8,16). Critically, such patients also have visual deficits for nonorthographic stimuli such as checkerboards and faces (15,17,18), supporting the primary systems view that this brain region is a more general visual-processing area.…”
mentioning
confidence: 94%
“…The visually based reading deficit sometimes termed "pure alexia" is associated with damage to the left ventral occipitotemporal cortex (14,15), an area that is ubiquitously activated for tasks involving orthographic processing (8,16). Critically, such patients also have visual deficits for nonorthographic stimuli such as checkerboards and faces (15,17,18), supporting the primary systems view that this brain region is a more general visual-processing area. In a similar vein, patients with phonological dyslexia have concomitant phonological deficits in tasks that do not involve written words (19)(20)(21).…”
mentioning
confidence: 94%